The Spanish dependencies in South America. An introduction to the history of their civilisation (1914)
This book aims to present an account of the second, or middle, period of the Spanish rule in South America, wich is marked by the organisation and development of political societies dependent on Spain, and lies between 1550 and 1730. It treats of the beginnings of European civilisation in widely separated regions of South America, and sets forth some of the characteristic events associated with the slow development of colonial communities.